THE DEVELOPMENT OF STUDENT WORKSHEET TO TRAIN CRITICAL THINKING SKILL IN ACID BASE MATTER FOR SENIOR HIGH SCHOOL IN 11th GRADE (UNESA Journal of Chemical Education, 2019)
This study aimed to produce appropriate student worksheet used as a teaching material to train critical thinking skill of acid-base matter that are reviewed from content validity and constructs through the results of validation by experts, practicality through student activities and student responses, and effectiveness through critical thinking skills and learning outcomes of student. The type of this research is the development of Research and Development (R&D) models which are limited to reaching the product trial stage. The student worksheet was tested on 12 students of 11th grade at SMAN 1 Sumberrejo Bojonegoro. Based on the research data obtained, student worksheet to train student critical thinking skills in acid-base matter developed is feasible to use, in terms of validity, practicality, and effectiveness. The results showed that the developed student worksheet was valid in terms of content validity, obtained a percentage of 91.99% and construct validity consisting of presentation criteria obtained a percentage of 88.37%, linguistic criteria obtained a percentage of 85.79%, and graphics criteria obtained a percentage amounting to 88.45%. student worksheet is practical in terms of observations of the activities of students during the testing phase of the student worksheet with a percentage of 96.36% and responses of students to each criterion namely the content criteria of 94.45%, presentation criteria 91.67%, linguistic criteria 91.67%, graphics criteria 97.23%. Effectiveness of student worksheet in terms of indicators of critical thinking skills consisting of interpretations obtained a percentage of 89.72% in the high category, analysis obtained a percentage of 86.17% in the high category, and inference obtained a percentage of 92.92% in the very high category. Increasing the results of the assessment of critical thinking skills through the n-gain score of 16.67% increased with medium category and 83.33% with high category, and the knowledge learning outcomes of students 100% scored above the KKM set at SMAN 1 Sumberrejo, namely >75. Keywords: Student Worksheet, Critical Thinking Skills, Feasibility, Acid Base